The influence of gender and bruxism on human minimum interdental threshold ability (Journal of Applied Oral Science, 2009)
OBJECTIVE: To evaluate the influence of gender and bruxism on the ability to discriminate minimum interdental threshold. MATERIAL AND METHODS: One hundred and fifteen individuals, representing both genders, bruxers and non-bruxers, with a mean age of 23.64 years, were selected for this study. For group allocation, every individual was subjected to a specific physical examination to detect bruxism (performed by three different examiners). Evaluation of the ability to discriminate minimum interdental threshold was performed using industrialized 0.010 mm-, 0.024 mm-, 0.030 mm-, 0.050 mm-, 0.080 mm- and 0.094 mm-thick aluminum foils that were placed between upper and lower premolars. Data were analyzed statistically by multiple linear regression analysis at 5% significance level. RESULTS: Neither gender nor bruxism influenced the ability to discriminate minimum interdental threshold (p>;0.05). CONCLUSIONS: Gender and the presence of bruxism do not play a role in the minimum interdental threshold.